Deconstructing Paradoxes Of Work Through CLA : Millennium Project Special Session at FFRC Conference ‘Futures of Natural Resources’, 13 June 2024, Turku, Finland - Heinonen, Sirkka; Ebrahimabadi, Samaneh; Viitamäki, Riku; Taylor, Amos; Pätikangas, Paula; Knudsen, Mikkel; Tähtinen, Lassi (Finland, 2026)
This report documents the process and results of the Millennium Project Special Session that was organised within the Finland Futures Research Centre (FFRC) Conference in Turku, Finland on 13th June, 2024. The MP Session was conducted within the FFRC research project T-winning Spaces 2035 that is ongoing at University of Turku, studying futures of work, work spaces, and new paradigm of work. The Twinning Spaces 2035 is a research project funded by the Research Council of Finland, and the European Union NextGenerationEU. It is headed by Aalto University with University of Turku and University of Tampere as partners. The Session was organised in co-operation between University of Turku, Aalto University, Millennium project, and the Finnish Society for Futures Studies. The session was arranged as an interactive futures clinique, with initial futures provocation followed by small group working on five paradoxes by applying a new foresight technique called ‘paradox probing’. The session thus provided a methodological experimentation where paradoxes were deconstructed via CLA (Causal Layered Analysis) and narratives for five different futures of work were sketched.